Association between use of different long-term care services and risks of mental disorder and mortality as well as medical utilization - Tseng, Pei-Ying; Wu, Chia-Ling; Chen, Jen-De; Ma, Kai-Jie; Yao, Chi-Yu; Wang, Jong-Yi (Frontiers in psychiatry, 2023)
This study sought to investigate mental disorder and mortality risks and medical utilization among various long-term care (LTC) services and examine the associated factors. This retrospective cohort study used data from the National Health Insurance Research Database of the entire population of Taiwan recorded between 2006 and 2017. A total of 41,407 patients using LTC (study group) were identified and propensity score-matched with 41,407 LTC nonusers (control group) at a ratio of 1:1 according to sex, age, salary-based premium, comorbidity index score, and urbanization level. Patients were divided into four groups according to LTC service type. The age distribution was as follows: 50-60 years (10.47%), 61-70 years (14.48%), 71-80 years (35.59%), and 81 years and older (39.45%). The mean age was 70.18 years and 53.57% of female participants were included. The major statistical methods were the Cox proportional hazards model and the general linear model (GLM). Users of both institutional and inhome LTC services had the highest risk of mental disorder [adjusted hazard ratio (aHR) = 3.2]. The mean mortality rate in LTC nonusers was 46.2%, whereas that in LTC users was 90.4%, with the highest found among the users of both institutional and inhome LTC (90.6%). The institutional LTC users had the shortest survival time (4.1 years). According to the adjusted Cox model analysis, the odds of mortality was significantly higher among institutional LTC users than among inhome LTC users (aHR = 1.02). After the adjustment of covariates, adjusted GLM model results revealed that the annual medical expenditure of LTC nonusers was NT$46,551, which was 1.6 times higher that of LTC users. Users of both institutional and inhome LTC services have higher risk of mental disorder, shorter survival time, and lower medical utilization.